Trends of Academic Publications: A Case Study of Malaysian Research Universities - Mohd Sarjidan, Mohd Arif; Md Kasim, Azrin (Journal of Research Management and Governance, 2023)
The Ministry of Higher Education Malaysia granted five universities with Research University (RU) status, which are Universiti Malaya (UM), Universiti Putra Malaysia (UPM), Universiti Kebangsaan Malaysia (UKM), Universiti Sains Malaysia (USM), and Universiti Teknologi Malaysia (UTM). These RUs are expected to focus on research and innovation and become a model of Malaysian universities for research activities aimed at knowledge advancement. Publications are one of the performance indicators for RUs. Thus, this paper confined its scope to the publications produced from 2016 to 2020 by the five RUs. The study aimed to analyse the patterns related to the number of publications, subject areas, type of publications, international joint publications, and the language of the publications. The findings show that the number of publications increased for UPM, UKM, and USM over five years, while UTM champions four subjects: Engineering, Materials Science, Computer Science, and Environmental Science. Journal articles are the most prominent scholarly output for all RUs. All RUs actively collaborate with international scholars and use English as the primary language for publications.